THE EFFECT OF REGIONAL ORIGINAL INCOME AND INVESTMENT ON ECONOMIC GROWTH IN LUWU EAST REGENCY, SOUTH SULAWESI PROVINCE - Achsanuddin UA, Anur; Anggoro KR, M. Yusuf Alfian Rendra; Masrullah, Masrullah; Mappa, Muhammad Rizal (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
This study aims to determine the effect of regional original income (PAD) and investment on economic growth in East Luwu Regency, South Sulawesi Province. The type of research used in this research is quantitative research. The data processed is secondary data from Regional Original Income, Investment and Economic Growth in East Luwu Regency, South Sulawesi Province in 2011-2020. The results of the study show that simultaneously Regional Original Income and Investment have a significant effect on Economic Growth in East Luwu Regency, South Sulawesi Province, this is evidenced by the significance value is smaller than the probability (0.010 < 0.05). Partially Local Original Income (PAD) has a significant effect on economic growth in East Luwu Regency, South Sulawesi Province, as evidenced by the significance value is smaller than the significance probability value (0.027 < 0.05) and partially Investment has a significant effect on economic growth in East Luwu Regency, Province South Sulawesi, as evidenced by the significance value is smaller than the significance probability value (0.030 < 0.05).